2013
DOI: 10.1016/j.mjafi.2012.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of healthcare associated infection in the surgical ICU of a tertiary care hospital

Abstract: The HAI rates in our ICU are less than other hospitals in developing countries. The incidence of VAP is comparable to other studies. Institution of an independent formal infection control monitoring and surveillance team to monitor & undertake infection control practices is an inescapable need in service hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
4
30
4
Order By: Relevance
“…Malhotra S. et al 5 observed that the infections was more among male than female. The increased incidence in geriatric age group may be due to their defective host defense mechanism was in accordance with other studies like Graves N. et al 2 and Malhotra S. et al 5 Similarly with respect to the role played by invasive devices in contributing to HAI, present study showed that 38% of UTI occurred in catheterised patients, 41.10% of pneumonia was associated with mechanical ventilation, 17.70% of bloodstream infections with catheter and 3.20% of local infections could be attributed to the use of invasive devices.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Malhotra S. et al 5 observed that the infections was more among male than female. The increased incidence in geriatric age group may be due to their defective host defense mechanism was in accordance with other studies like Graves N. et al 2 and Malhotra S. et al 5 Similarly with respect to the role played by invasive devices in contributing to HAI, present study showed that 38% of UTI occurred in catheterised patients, 41.10% of pneumonia was associated with mechanical ventilation, 17.70% of bloodstream infections with catheter and 3.20% of local infections could be attributed to the use of invasive devices.…”
Section: Discussionsupporting
confidence: 92%
“…1 Considerable increased mortality and major costs are associated with ICU-acquired infections. [3][4][5] Hospital-Acquired Infections (HAI) are a cause of prolonged hospital stay are inconvenient for the patient, constitute an economic burden on health care and increase the mortality of hospitalised patients. 4 The HAI was defined according to Centres for Disease Control and Prevention Standards.…”
Section: Introductionmentioning
confidence: 99%
“…3) We achieved a more rapid turnover of patients in the present study as compared to the previous one, 34.78% in the present study as compared to 69.6% patients in the prior study stayed for more than 48 h in the ICU. 1 Thus part of the results achieved may have been because the stay of patients in the ICU was minimized. Since a number of interventions had been instituted at the same time, we cannot postulate the effect of each specific intervention towards the final result.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study settings are similar and measurement bias has been effectively taken care of since the present study was done on the same lines as the previous one with which the results are being compared. 1 However, since it would not have been ethical to subject one group of patients to inadequate care as compared to the interventions being implemented we decided to use the previous study for comparison. Moreover, even though the interventions instituted are known facts, there is hardly any data regarding the incidence of nosocomial infections in service ICU's or the effect of infection control interventions in the service setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation